Laying the groundwork: Building relationships for public and patient involvement in pre‐clinical paediatric research - Wendy Costello; Emma Dorris (Wiley, 2020)
Abstract Context Public and patient involvement is increasingly becoming an expectation of research funders and policy makers. Not all areas of health research are public‐facing. Here, we outline an approach for building the skills and developing the relationships required for downstream public and patient involvement in pre‐clinical adolescent rheumatology research. Objective To design a methodology for improving researcher‐adolescent communications specifically aimed at mutual relationship building for PPI. Deliberate and effective preparation in advance of research involvement to improve the downstream success of that involvement. Design A research seminar and research skills workshop conducted entirely in 'plain English' for adolescents and their siblings aged 10‐20. Upskilling of pre‐clinical researchers for effective public involvement. Setting and participants Study co‐design between the voluntary charity Irish Children's Arthritis Network and the academic research centre UCD Centre for Arthritis Research. Fifteen adolescents aged 10‐20 years old living with arthritis, four pre‐clinical researchers and one qualitative researcher investigating adolescent or paediatric arthritis. Main variables studied Relationship building and communications for effective downstream public involvement in pre‐clinical and laboratory research. Results The methodology outlined here was received extremely positively. Both researchers and adolescents living with arthritis felt more comfortable communicating, more knowledgeable about juvenile arthritis and research, and more able to engage in co‐operative dialogue. Discussion Engaging early, considering the needs of the community and developing appropriate involvement methodology can enable involvement in pre‐clinical research. Conclusions Dedicating resources to building relationships and skills necessary for co‐operative research involvement can overcome some of the barriers to public involvement in pre‐clinical and laboratory‐based research.